Exploring the physiological state of continental Antarctic endolithic microorganisms by microscopy - Ríos, Asunción de los; Wierzchos, Jacek; Sancho, Leopoldo G.; Ascaso, Carmen (FEMS Microbiology Ecology, 2004)
10 pages, and photos, and tables statistics. In this microscopy study, we show that microorganisms comprising many endolithic communities of the McMurdo Dry Valleys of Antarctica appear in different physiological states. Live/dead microbial fluorescence stains were used to identify the state of microorganisms in the biofilms. The ultrastructures of these microorganisms were then characterized by transmission electron microscopy. Cyanobacteria were associated with heterotrophic bacterial cells, while fungal cells were free-living or formed partners with green alga as lichens. The extracellular polymeric substances, in which the endolithic microorganisms were embedded, formed an integral part of the biofilms observed. Extracellular polymeric substances probably play a significant role in nutrient interactions and protection of microorganisms from the environmental conditions outside the film. Living, moribund, dormant and dead microorganisms shared this microhabitat. The ecological impacts of the observed physiological dynamics are discussed. Peer reviewed